(untitled) (CITITORI ȘI LECTURI. CERCETĂRI COMPARATISTE, 2026)
Fabiana Florescu explores the literary Hell in Mohamed Mbougar Sarr’s The Most Secret Memory of Men. The study analyzes the labyrinthine journey of narrator Diégane Faye as he searches for the mysterious T.C. Elimane. Drawing on Maurice Blanchot’s theories, the author highlights the conflict between expression and silence. Ultimately, the quest becomes a metadiscursive reflection on the "absence of the work," where literature serves as both a demonic trap and a vital means of survival. THIS ABSTRACT IS GENERATED WITH ARTIFICIAL INTELLIGENCE.